Anthocyanins from Lycium ruthenicum Murray Mitigate Cadmium-Induced Oxidative Stress and Testicular Toxicity by Activating the Keap1/Nrf2 Signaling Pathway - Mingran Dong; Juan Lu; Hongwei Xue; Yang Lou; Shuyang Li; Tao Liu; Zimian Ding; Xi Chen (MDPI AG, 2024)
Cadmium (Cd) is a hazardous heavy metal environmental pollutant that has carcinogenic, teratogenic, and mutagenic properties. Excessive exposure to Cd can induce oxidative stress, which greatly harms the male reproductive system. Anthocyanins have remarkable antioxidative, anti-inflammatory, and anti-stress properties. In this study, we investigated the effects of anthocyanins and the underlying mechanisms through which anthocyanins mitigate Cd-induced reproductive damage. We isolated and purified Lycium ruthenicum Murray anthocyanin extract (LAE) and performed UHPLC-MS/MS to identify 30 different anthocyanins. We established an ICR mouse Cd injury model by administering 5 mg/kg/day CdCl2 for 28 consecutive days. LAE at 500 mg/kg/day effectively ameliorated testicular damage and preserved spermatogenesis. The mice in the LAE-treated group had elevated testosterone and inhibin B levels. Additionally, the treatment restored the activity of antioxidant enzymes, including T-SOD, CAT, and GR, and substantially increased the levels of the non-enzymatic antioxidant GSH. Research findings indicate that LAE can activate the SIRT1/Nrf2/Keap1 antioxidant pathway. This activation is achieved through the upregulation of both the SIRT1 gene and protein levels, leading to the deacetylation of Nrf2. Moreover, LAE reduces the expression of Keap1, alleviating its inhibitory effect on Nrf2. This, in turn, facilitates the uncoupling process, promoting the translocation of Nrf2 to the nucleus, where it governs downstream expression, including that of HO-1 and GPX1. LAE effectively mitigated toxicity to the reproductive system associated with exposure to the heavy metal Cd by alleviating oxidative stress in the testes.